Resolusi Konflik Antar-Santri dengan Pendekatan Musyawarah dan Islah - asna asna; Akhmad Zaeni (Universitas Al-Falah As-Sunniyah Kencong Jember, 2024)
Inter-santri conflict is a dynamic that often arises in the pesantren environment, which if not managed properly can disrupt community harmony and the educational process. This study aims to analyse the application of deliberation and islah approaches in resolving inter-santri conflicts in pesantren. The research method used is a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The results showed that deliberation is effective in creating an open dialogue space, where each party can express their views and seek solutions together equally. The islah approach, which emphasises peace and restoration of relationships, is able to minimise the impact of conflict and strengthen ukhuwah among santri. The combination of deliberation and islah results in a resolution that not only resolves the conflict, but also builds justice, unity, and harmony in pesantren life. This research recommends strengthening the values of deliberation and islah in pesantren life through integration in character education and santri development programmes. Thus, this approach can be a relevant conflict resolution model, not only for pesantren, but also in a broader social context.